Parcerias público-privadas em educação: novos arranjos na agenda internacional da educação - Silva, Filomena Siqueira e (2015)
The deepening of globalisation dynamics over the last decades has boosted the influence of organizations and global networks of multiple actors who work in the field of educational policies. The deterritorialization movement of policy-making creates new spaces for initiatives of different nature, both from the point of view of its sphere of action and the actors involved. In the context of these new connections, initiatives marked by the involvement of the private sector in public education have been developed in a complex arrangement referred to as public-private partnerships in education. This research analyzes these partnerships in education, that arise in a scenario of transformations on the functioning and organization of States and within the relations established beyond its borders. In view of the complexity of the subject and in order to investigate how it is translated and developed locally, three contexts are analyzed in greater depth: Chile, with its system of subsidized schools, the United States, with charter schools and the Netherlands, which has historically structured its educational system from the concept of school choice. From the conceptual analysis on public-private partnerships in education and by deepening the research in these representative cases, this dissertation seeks to problematize this arrangement over public policies for education and highlight how their development is articulated with institutions and processes that transcend the framework of Nation -States.